ANALISIS JUMLAH TENAGA KESEHATAN DI JAWA TIMUR TAHUN 2022-2023 MENGGUNAKAN METODE RM MANOVA SATU ARAH - Khufi, Rijal Apuila; Gunawan, Jovanka Vania; Nainggolan, Ester Yunita; Muhammad Nasrudin; Trimono Trimono (CV. Denasya Smart Publisher, 2025)
In 2020, the COVID-19 pandemic had a significant impact on the healthcare sector in Indonesia, including the number and distribution of healthcare workers. Entering the recovery phase in 2022, various changes occurred in the healthcare employment system, which could affect the number of healthcare workers in different regions, including East Java Province. This study aims to analyze the differences in the number of healthcare workers in East Java between 2022 and 2023 using the Multivariate Analysis of Variance (MANOVA) method. In this study, multivariate normality was tested using Mardia's method, while the homogeneity of the covariance matrix was analyzed through Box's M test. The results of the tests indicated that the data met these assumptions, allowing MANOVA to be properly applied to identify the variables influencing the differences in the number of healthcare workers in East Java. These findings are expected to assist policymakers in designing a more effective distribution plan for healthcare workers.